The concept of “tourist destination” and its specific features - V. V. Makaryushchenko (Аграрная наука Евро-Северо-Востока, 2018)
The article analyzes the concept of “tourist destination” in reference to the hunting tourism, speaking of which only a territory inhabited by some kind of game can be called a destination. The paper introduces a relatively new term for the science of game management in Russia, a “tourist hunting destination”. The tourist hunting activity is known to occur and develop in the territorial natural complexes having definite natural and economic characteristics which allow for hunting for certain types of game. To describe them as natural and socio-economic phenomena, the term of “tourist hunting destination” is increasingly used. In the article this concept is given definition and characteristic in view of modern concepts that have been developed on carrying out hunting tourism studies. It is shown that the tourist hunting destination can be characterized as a physical and geographical territory and socio-economic area within the boundaries of the subject of the Russian Federation, where hunting resources are attractive for hunters. The functions of managing the protection, reproduction and regulation of the use of these areas are carried out by authorized federal agencies. The scheme of interaction of the territorial executive authority and economic entities in the sphere of hunting tourism regarding the use of game resources is suggested. The criteria of the tourist hunting destination are proposed. Several phases of development of tourist hunting destinations are identified and the main factors that limit their capacity are determined. It is shown that the most important feature that characterizes the image of a tourist hunting destination is the quality of its hunting trophies and services provided for bagging of game, correlated with the price. It is concluded that the tourist hunting destination is one of the important components in hunting tourism.